Perancangan Dan Pengujian Pompa Sebagai Turbin Untuk Pembangkit Listrik Tenaga Air - Fadjrin Cahyani Sangadji La Ada; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
A pump as a turbine is a pump that is converted from a motor-driven pump to bring water, becomes driven by falling water and then turns the impeller and transformed it into a mechanical energy. Basically the Working Principle of the Pump as a Turbine is a pump that is in a state of being sedated by water at a certain height. The water will rotate the impeller, then the impeller is then passed to a generator that converts it to mechanical energy. Testing and designing the pump as a turbine aims to analyze the method of manufacture and processes for pumps designed by students. In Riau Province itself no one has used a pump as a replacement for turbines to generate electricity. Pump design as a turbine consists of searching the value of the initial variable, calculation and design. From testing the pump as a turbine that has been designed, the data shows that the largest potential hydro power is 3169 watts and potential pump power is 5003 watts. From the potential power that has been obtained it is known that the design of the pump as a turbine is feasible to use as a power plant.Keywords : Pump, Turbine, Picohydro,